Discontinuation and non‐publication of neurodegenerative disease trials: a cross‐sectional analysis. (21st June 2017) - Stefaniak, J. D.; Lam, T. C. H.; Sim, N. E.; Al‐Shahi Salman, R.; Breen, D. P.
Abstract : Background and purpose: Trial discontinuation and non‐publication represent major sources of research waste in clinical medicine. No previous studies have investigated non‐dissemination bias in clinical trials of neurodegenerative diseases. Methods: ClinicalTrials.gov was searched for all randomized, interventional, phase II–IV trials that were registered between 1 January 2000 and 31 December 2009 and included adults with Alzheimer's disease, motor neurone disease, multiple sclerosis or Parkinson's disease. Publications from these trials were identified by extensive online searching and contact with authors, and multiple logistic regression analysis was performed to identify characteristics associated with trial discontinuation and non‐publication. Results: In all, 362 eligible trials were identified, of which 12% (42/362) were discontinued. 28% (91/320) of completed trials remained unpublished after 5 years. Trial discontinuation was independently associated with number of patients ( P  = 0.015; more likely in trials with ≤100 patients; odds ratio 2.65, 95% confidence interval 1.21–5.78) and phase of trial ( P  = 0.009; more likely in phase IV than phase III trials; odds ratio 3.90, 95% confidence interval 1.41–10.83). Trial non‐publication was independently associated with blinding status ( P  = 0.005; more likely in single‐blind than double‐blind trials; odds ratio 5.63, 95% confidence interval 1.70–18.71), number of centres ( P  = 0.010; more likely in single‐centre than multi‐centre trials; odds ratio 2.49, 95% confidence interval 1.25–4.99), phase of trial ( P  = 0.041; more likely in phase II than phase IV trials; odds ratio 2.88, 95% confidence interval 1.04–7.93) and sponsor category ( P  = 0.001; more likely in industry‐sponsored than university‐sponsored trials; odds ratio 5.05, 95% confidence interval 1.87–13.63). Conclusions: There is evidence of non‐dissemination bias in randomized trials of interventions for neurodegenerative diseases. Associations with trial discontinuation and non‐publication were similar to findings in other diseases. These biases may distort the therapeutic information available to inform clinical practice.